Dynamic modeling of a three-dimensional braided composite thin plate considering braiding directions - Gao, Chentong; Sun, Huiyu; Gu, Jianping; Huang, W. M. (Applied mathematics and mechanics, 2025)
Currently, there are a limited number of dynamic models available for braided composite plates with large overall motions, despite the incorporation of three-dimensional (3D) braided composites into rotating blade components. In this paper, a dynamic model of 3D 4-directional braided composite thin plates considering braiding directions is established. Based on Kirchhoff’s plate assumptions, the displacement variables of the plate are expressed. By incorporating the braiding directions into the constitutive equation of the braided composites, the dynamic model of the plate considering braiding directions is obtained. The effects of the speeds, braiding directions, and braided angles on the responses of the plate with fixed-axis rotation and translational motion, respectively, are investigated. This paper presents a dynamic theory for calculating the deformation of 3D braided composite structures undergoing both translational and rotational motions. It also provides a simulation method for investigating the dynamic behavior of non-isotropic material plates in various applications.